Analysis of Surakarta Regional Regulation Number 9 of 2019 about Smoke Free Areas - Arif Faozi; Vicki Dwi Purnomo; Syukron Abdul Kadir; Benedictus Hestu Cipto Handoyo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Government Regulation No. 109/2012 contains provisions that every region must have a KTR regional regulation, as well as Article 115 paragraph (2) of Law Number 36 of 2009 concerning Health states that Regional Governments are required to establish smoke-free areas in their territories. Based on data from the Ministry of Health until now, there are already 418 regions or around 67% that have KTR regulations, to follow up on policies issued by the government, the Surakarta City Government issued Regional Regulation No. The results of the study show that the implementation of Regional Regulation Number 9 of 2019 concerning KTR in the Jebres Surakarta Smart Park is not good enough or not optimal enough. This is because there are still deficiencies such as a lack of communication in the form of direct socialization and the results of the policy cannot be said to be directly proportional to the objectives of the policy where there is a lack of a sense of firmness from the executors in reprimanding and there is still a weak awareness in society that is not optimal.